A hipermídia como viabilização da ética na administração pública federal : propostas de um modelo de ação para produção de conteúdo jornalístico no IFSULDEMINAS - Bueno, José Valmei (2018)
The Ethics of public organizations and systems require the construction of mechanisms for an open, transparent and democratic relationship between Society and State. The contemporary Information and Communication Technologies benefit the interactivity between citizens and federal institutions. One of the most effective means of stopping plural communication between individuals and public organizations is the journalistic-editorial content built on institutional websites.In the twenty-first century, when hyper-mediatic language shows a powerful power of influence over society,the State can not give up implementing it in its communication systems, which requires public management to re-orient cultural in the establishment of the conversation with individuals.That is, in the context of hypermedia, the information generated within public organizations is not elaborated by the logic of monologue, but is constructed by the diversity of opinions; they are not restricted to certain interest groups, but are exposed and built up instantly in cyberspace.Thus, the state institutions must adapt the language of journalistic content conveyed by institutional portals to the characteristics of this contemporary medium of communication to enhance ethics in the federal public service.The aim of this research is to analyze the journalistic content that was published on the institutional website of Instituto Federal de Educação, Ciência e Tecnologia from the South of Minas Gerais State, Brazil.(IFSULDEMINAS) apart from the ethical concepts housed in the Code of Conduct of the Federal High Administration, which t will have as its main goals, to present ethical guidelines for the dissemination of hypermedia journalistic content in a Federal eduacational institution ( IF Sul de Minas). For this, the exploratory research methodology will be pursued, fundamentally through literary review and in-depth interviews though. As a result, technical, cultural and political / economic proposals were obtained for the execution of a Model of Action.